2012
DOI: 10.1007/s12149-012-0648-6
|View full text |Cite
|
Sign up to set email alerts
|

Time course of bone metabolism at the residual ridge beneath dentures observed using 18F-fluoride positron emission computerized-tomography/computed tomography (PET/CT)

Abstract: ObjectiveExcessive pressure due to wearing mal-adapting dentures is well known to cause residual bone resorption beneath the denture. X-rays have been commonly utilized to evaluate the changes in the bone beneath the denture. However, X-ray images merely detect bone density and relatively large changes in the bone shape and structure, whereas nuclear medicine imaging can detect functional changes, which occur prior to structural changes. This article aimed to describe the time course of the bone metabolism at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Despite no clinical problem on the abutment tooth, such as pain or increasing tooth mobility, the SUV of alveolar bone in Subject A reached a high value of 14·8, a possible level indicating tumour . The previous study reported this bone metabolic changes were temporary . In the other word, even a well‐adapted denture can change the bone metabolism significantly for the first‐time denture user, though temporarily.…”
Section: Discussionmentioning
confidence: 83%
“…Despite no clinical problem on the abutment tooth, such as pain or increasing tooth mobility, the SUV of alveolar bone in Subject A reached a high value of 14·8, a possible level indicating tumour . The previous study reported this bone metabolic changes were temporary . In the other word, even a well‐adapted denture can change the bone metabolism significantly for the first‐time denture user, though temporarily.…”
Section: Discussionmentioning
confidence: 83%
“…However, the level of mAs on 18 F-NaF or 18 F-FDG PET/CT studies is a matter of discussion and a wide range of values may be found in the literature ( 15 , 16 ) . With the use of phantoms, some researchers have demonstrated that CT tube current intensity as low as 10 mAs could be appropriate to perform attenuation correction on PET/CT studies ( 24 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are scarce studies in the literature on the most appropriate mAs values. In the literature it is possible to find values ranging from 15 mAs ( 15 ) to 95 mAs ( 16 ) . Therefore, it is necessary to evaluate the adequate mAs values in light of current advances in technology as well as the ALARA principles.…”
Section: Introductionmentioning
confidence: 99%
“…The fluoride ion exchanges with the hydroxyl group in the bone mineral hydroxyapatite crystal to form fluoro apatite. 15,21 Therefore, tracer uptake reflects bone remodel ing and represents vascularized vital osseous tissue. The images showed uptake within the entire implant with a marked intensity at the anterior part, providing evidence of bone formation.…”
Section: Illustrative Casementioning
confidence: 99%